Between Culture and Curricula: Exploring Student and Faculty Experiences of Undergraduate Research and Inquiry - Perrella, Andrew; Dam, Huyen; Martin, Lynn; MacLachlan, John C.; Fenton, Nancy (Teaching and Learning Inquiry, 2020)
Undergraduate research and inquiry is a growing movement within the teaching and learning nexus, with many institutions developing their practices within this culture of education. This study aimed to identify the perceptions and experiences surrounding undergraduate research and inquiry among students and faculty at McMaster University in Ontario, Canada; assess the extent of research and inquiry in the design of undergraduate courses; and explore the facilitators and obstacles educators encounter when attempting to implement this educational approach. Although differences exist in student and faculty definitions of undergraduate research and inquiry, we found two principal models that characterize its structure and delivery—the scaffold model and bookend model. A third, the abstract model, does not employ the practice of inquiry. Despite numerous benefits unique to undergraduate research and inquiry education identified by stakeholders, notable barriers (such as funding, faculty buy-in, limited student experience, and inherent competition) hinder its progress. Overall, we found a diversity of undergraduate research and inquiry practices across the university, operating within varying cultures and comfort levels, which suggests unequal access for student learners.